Pemanfaatan Kartu BPJS Ketenagakerjaan Sebagai Kartu Diskon Tinjauan UU Ketenagakerjaan dan Maslahah Mursalah - afiffudin afiffudin (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The purpose of this research is to know the juridical validity of the BPJS Employmentcard utilization as a discount card review labor law and Islamic law. This research included in this type of normative or legal research legal research library which is done by examining the material law of primary and secondary legal materials. The primary legal materials obtained directly from the source at first, but in this study the primary legal materials used, namely law No. 13 Year 2003 concerning Employment. Secondary legal material in this case authors use legal research journals that are related to the theme of the research, as well as books that explain about the concept of employment, BPJS multiakad (contract Murakabah) and al-mursalah al-maslahah. The results of this study showed that the utilization of Labor as the BPJS card discount card is not listed in the BPJS Employment legislation. Review of Islamic law against the contract used in the utilization of Employment was multikad BPJS card (contract Murakabah) and the concept of maslahah al-al-mursalah, thus the utilization of Labor as the BPJS card discount card can be take advantage of discounted rates for all as the transaction is the purchase of products or services.